A tale of a flower girl constructing a narrative using traditional and non-traditional painting materials - Non, Maria Grasha L.; Abaño, Ma. Victoria; Romero, Riza (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
This thesis explores the world of my imagined narrative. This imagined narrative serves as an autobiographical story told in the manner of a fantasy. It is shown through the character of a flower headed girl, wanting to discover her head. This narrative is a reflective of my own experiences and have been transformed into imagery using fantasy. I have constructed these concepts through the help of the theories articulated by Carl Jung's process of individuation. Sublimation as discussed separately by Freud and Jung and the commentaries of Joseph Campbell. The imageries that I am using are drawn from the process of suggestivism, visionary arts, psychedelic art and fantasy art; where images are stories flowing from my imagination told in my paintings. The outputs of this thesis are six 2.5 ft by 3.5 ft and one 6ft by 4ft mixed media paintings that explore materials that contribute to my persona of girlishness, such as glitters, beads, organza cloth to show the phantasm of the narrative of the flower headed girl.
Thesis (Bachelor in Fine Arts (Painting))--University of the Philippines Diliman
Bibliography : leaves 19-20.
Keywords: Narrative art; Psychedelic art